A multigene phylogeny and timeline for Trichoptera (Insecta). (6th February 2020) - Thomas, Jessica A.; Frandsen, Paul B.; Prendini, Elizabeth; Zhou, Xin; Holzenthal, Ralph W.
Abstract : The Trichoptera, or caddisflies, are traditionally split into two taxonomic subdivisions: the 'retreat‐making' Annulipalpia and the 'case‐making' Integripalpia (sensu Ross). The monophyly of these groups is well documented; however, the establishment of a third subdivision, 'Spicipalpia', and the positions of the five 'spicipalpian' families is much debated. In contrast to previous molecular studies using nuclear ribosomal RNA, a recent trichopteran study (using nuclear protein‐coding genes) placed one of these 'spicipalpian' families, the free‐living predatory Rhyacophilidae, as the sister taxon to the rest of Trichoptera, a result that has significant implications for both the understanding of trichopteran evolution and its timing. This paper sets out to investigate the relationships of Trichoptera using several newly sequenced genes, together with previously published gene sequences. This dataset is the largest trichopteran dataset to date, covering six independent genes and > 10 000 nucleotides, and containing 185 species representing 49 families. With all data included, likelihood and Bayesian analyses support a monophyletic Annulipalpia and a monophyletic Integripalpia, which includes the 'spicipalpians' as a paraphyletic grade at the base of this clade. However, an analysis of the protein‐coding data alone using similar analytical methods recovers Rhyacophilidae as the most basal taxon in Trichoptera, with low support. A reanalysis correcting for nucleotide composition bias provides support for the placement of the 'spicipalpian' taxa as sister to the Integripalpia, consistent with the total data analysis, suggesting that the basal position of Rhyacophilidae in the uncorrected analysis could be (or is probably) an artefact of base composition. We find it likely that ancestral trichopterans made incipient cases and retreats, and these had independent origins as precocious pupal chambers. Molecular dating analysis in beast, using the birth‐death model of speciation, with a relaxed‐clock model of sequence evolution informed by 37 fossil constraints, suggests that the most recent common ancestor of Trichoptera appeared in the Permian ( c. 275 Ma) in line with the first appearance of Trichoptera in the fossil record, and that vicariance explains the distribution of most trichopteran taxa. A new infraordinal name, Phryganides, is introduced for the tube‐case‐making families of Integripalpia. Abstract : We present the largest maximum likelihood molecular phylogeny to date for the insect order Trichoptera, including 185 taxa across 49 families, and over 10 000 nucleotides. We use a relaxed‐clock dated phylogeny informed by 37 fossil constraints, estimated in BEAST, to discuss higher‐level phylogeny and biogeographical patterns, and non‐monophyly of 'Spicipalpia'. We find evidence that base compositional biases may have produced a previous unexpected trichopteran topology, with implications for ancestral character state reconstruction.